Influence of psychological, internet use and demographic factors on pathological internet use among university students - Lu, Xi (2015)
The purpose of this study was to identify the prevalence of Pathological Internet Use (PIU), to test the hypothesized structural model of Pathological Internet Use (PIU) and explore the relationship between cognitive distortion, depression, motivation, loneliness, stressful life events, and PIU. A total of 1493 undergraduate students from Universiti Teknologi Malaysia (UTM) were selected as respondents of this study. The results of this study showed an overall prevalence of PIU was 1.2% and there was no significant difference across groups (Massively multiplayer online role-playing game known as MMORPG, Social Networking Sites known as SNS, and general). The structural model of PIU demonstrated a good fit and all the variables were identified as significant predictors of PIU. Cognitive distortion was identified as the most significant predictor influencing PIU (Beta=0.47, p<0.01), and was confirmed as the most significant mediator between motivation (Beta=0.45, p<0.01), stressful life events (Beta=0.15, p<0.01), depression (Beta=0.39, p<0.01) and PIU. Motivation was found as the second significant predictor directly influencing PIU (Beta=0.35, p<0.01), while stressful life events was the lowest significant predictor directly influencing PIU (Beta=0.10, p<0.01). All the three factors contributed 65% variance of PIU. Besides this, depression was identified as the second significant mediator fully mediating the effect of loneliness on cognitive distortion (Beta=0.71, p<0.01) and partially mediating the effect of stressful life events on cognitive distortion (Beta=0.22, p<0.01). The multi-group analysis was applied to test the moderating effect of Internet use group (MMORPG, SNS, general) on the structural model. The result confirmed the invariance of the structural model across groups. The discussions of results were based on cognitive-behavioral model and previous literatures related PIU. It is recommended to conduct research on pathological Internet use (PIU) among university students as it can identify the status of their Internet use.